Examining Parental Perception of Inclusive Education Climate - Sharma, Umesh; Woodcock, Stuart; May, Fiona; Subban, Pearl (Frontiers in Education, 2022)
Parental perspectives on their child’s experience of inclusion at school have received limited attention in the literature. Considering parental voice plays an important role in determining the quality of inclusive education, it is important to examine parental experiences of their child's inclusion. The lack of reliable and valid tools has severely limited research in this area. One of the key objectives of this study was to build the evidence base in the field by testing the psychometric properties of the newly developed Parental Perception of Inclusion Climate Scale, which was developed using a systematic approach drawing on a review of available research in the field. The scale includes items regarding parental perspectives on six key aspects of inclusion: presence, participation, acceptance, achievement, happiness and belonging. Participants were recruited through social media, and data from 190 parents of children with a disability attending a range of school settings was collected. Results suggested a three-factor structure, with strong internal consistency for the scale. These factors were: Teacher and School Support; Student Engagement; and Friendships. The scale showed that parents are moderately satisfied with their child’s inclusion in school overall. A series of independent sample t-tests and one-way ANOVAs revealed significant differences in parental perspectives of inclusion as measured by the scale according to school sector, disability type and parent gender. Parents whose children attend government schools reported less satisfaction with their child’s inclusion and also with the support provided by teachers and schools more broadly, as compared to parents of children who attend independent schools. Results also suggested that parents of children with a social emotional disability reported less satisfaction with their child’s engagement in school as compared to parents of children without a social emotional disability. Finally, fathers reported higher levels of satisfaction with their child’s engagement in school and also higher levels of satisfaction with their child's peer relationships than mothers. This study provides a tool that researchers, school educators and policy makers could use to collect evidence about the efficacy of inclusive practices for students with a disability as well as guiding evidence-based practice and theory in inclusive education.